Reconceptualizing Professionalism In Vocational High School Graduates: A Multi-Stakeholder Perspective From Education and Industry - Kurniawan Harun Rasyid; Hamsu Abdul Gani; Riana T Mangesa (Jurnal Teknologi Pendidikan, 2026)
This study aims to reconceptualize professionalism among vocational high school graduates through a multi-stakeholder perspective involving vocational education institutions, higher education, and industry. The study addresses the persistent gap between graduate competencies and labor market demands, particularly in non-cognitive and identity-related aspects of professionalism. A qualitative conceptual approach was employed using an integrative literature review grounded in the framework of Personal Professional Theories (PPT), which views professionalism as a dynamic and context-dependent construct shaped by individual experience and reflection. The findings indicate that professionalism in vocational education cannot be adequately understood as a set of standardized competencies. Instead, it is a multidimensional construct consisting of three integrated dimensions: Universal, Exploration, and Investigation (UNI). The Universal dimension represents foundational competencies and professional values, the Exploration dimension emphasizes experiential and contextual learning processes, and the Investigation dimension focuses on reflective identity formation and personal professional development. Based on these findings, this study proposes a One-to-One Professionalism Development Framework that integrates personalized mentoring with structured learning experiences. The framework highlights the importance of continuous guidance, reflection, and individual development pathways in fostering professional identity and employability. This study contributes theoretically by shifting the understanding of professionalism from a competency-based model to a personalized and identity-based construct. Practically, it offers a conceptual foundation for developing adaptive and learner-centered vocational education models that align more closely with the evolving demands of the labor market. The proposed framework provides a basis for future empirical research and innovation in vocational education systems